Hubungan Antara Work Life Balance Dengan Kepuasan Kerja Pada Karyawan Di PT. Latexindo Toba Perkasa Binjai - Elisabeth Tampubolon; Merri Hafni (Universitas Medan Area, 2022)
The purpose of this research is to see the correlation between the work life balance and the job satisfaction on the employees of PT. Latexindo Toba Perkasa Binjai. The population of this research are the employees of PT. Latexindo Toba Perkasa Binjai, the amount of the population are 845 people, and the sample are 120 people, the sampling technique that used in this research is purposive sampling. The research method that used is quantitative methods. The correlation of the data uses work life balance scale and a job satisfaction scale which is measured of the data by using a likert scale. The data analysis technique that used is the Product Moment Correlation technique. The results of this research show the significance value of the correlation p = 0.000 0.05, it means there is a positive correlation between the work life balance and the job satisfaction on the employees of PT. Latexindo Toba Perkasa Binjai, with a determinant coefficient (r2) 0.473 or 47.3%. In other words, the hypothesis is accepted. The job satisfaction is classified as moderate leading to low (empirical mean = 74.21 hypothetical mean = 75 where the difference is more than SD = 22.198), and for work life balance is classified as moderate leading to low (empirical mean = 96.83 hypothetical mean = 105 where the difference is more than SD = 20,797).